1996
DOI: 10.1046/j.1365-2249.1996.d01-770.x
|View full text |Cite
|
Sign up to set email alerts
|

An analysis of apoptosis in lymphoid organs and lupus disease in murine systemic lupus erythematosus (SLE)

Abstract: SUMMARYApoptosis is a programmed cell death process that helps to regulate both T cell and B cell development. In this study, we have investigated the levels of apoptotic death in cells of the thymuses and spleens (white matter) of autoimmune MRL-lpr/lpr mice with progressive lymphadenopathy and SLE disease activity; we also examined the renal pathology in these animals. Fas is a cell surface receptor, which when activated initiates the sequence of events that lead to apoptosis. In MRL-lpr/lpr mice Fas is defe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

1998
1998
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(15 citation statements)
references
References 34 publications
1
14
0
Order By: Relevance
“…A few necrotic cells were also labelled using this method. Other studies have found similar inconsistencies with end-labelling methods (Ravirajan et al, 1996). The results of the present study confirmed that ISEL detected fewer cells as apoptotic than morphological analysis, but also showed that there was a significant relation between the fraction of ISEL positive cells and the severity of cerebral injury measured by MRS.…”
Section: Morphological Analysissupporting
confidence: 87%
“…A few necrotic cells were also labelled using this method. Other studies have found similar inconsistencies with end-labelling methods (Ravirajan et al, 1996). The results of the present study confirmed that ISEL detected fewer cells as apoptotic than morphological analysis, but also showed that there was a significant relation between the fraction of ISEL positive cells and the severity of cerebral injury measured by MRS.…”
Section: Morphological Analysissupporting
confidence: 87%
“…The MRL/ MpJ-Fas lpr (MRL/lpr) mouse is a prototypical model for human SLE in which the presence of a single gene mutation on the Fas (CD95) gene leads to reduced signaling for apoptosis (10). Actually, the impaired clearance of apoptotic cells favors the self-antigen presentation and the production of multiple autoantibodies, which represents the central immunological disturbance in murine SLE (11). Indeed anti-double-stranded DNA (anti-dsDNA) and antitissue transglutaminase (anti-tTG) IgGs (12), splenomegaly, and deregulated production of Th1 and Th2 cytokines (13) have been used as markers to monitor murine SLE disease progression.…”
mentioning
confidence: 99%
“…C4-deficient mice show a significant delay in the phagocytosis of apoptotic cells, but to a lesser degree than C1q-deficient mice [20]. C3 activation via both the classical and alternative pathways also promotes uptake of apoptotic cells by human macrophages [27]. Complement deficiency may increase autoantibody production by other mechanisms, for example, loss of C4-mediated negative selection of auto-reactive B lymphocytes [28].…”
Section: Discussionmentioning
confidence: 99%